Father Brown. Complete season ten [videorecording (DVD)] - Flowerday, Rachel (Screenwriter); Guner, Tahsin, 1972-; Chesterton, G. K. (Gilbert Keith), 1874-1936 (BBC Studios, 2023)
"The year is now 1954 and the sleepy Cotswold village of Kembleford sees new faces join Father Brown's team of sleuths. The dashing Chief Inspector Sullivan is back and proves a pleasant distraction for Mrs Devine, Father Brown's lively new Parish Secretary, while plucky new housekeeper Brenda helps the priest's crime solving. With royal visits, kidnappings and notorious gangsters to contend with, Father Brown also faces his old adversary Flambeau who returns to Kembleford after being accused of murder. Father Brown risks his own life to prove his innocence--but is his faith in Flambeau misplaced?"--Container.